Unicameral (simple) and aneurysmal bone cysts: the effect of insufficient curettage on recurrence - Celik, Suat; Uludag, Abuzer; Tosun, Haci Bayram; Serbest, Sancar; Gurger, Murat; Kilic, Sabahattin (African Field Epidemiology Network-Afenet, 2016)
Introduction: Curettage of the cyst and bone grafting are the most common methods used in the treatment of unicameral bone cysts (UBC) and aneurysmal bone cysts (ABC). Recurrence of these cysts is often associated with insufficient curettage of the cyst during surgery. In this study, we aimed to evaluate the effect of insufficient curettage on recurrence in patients with UBC and ABC. Methods: The retrospective study included 18 patients with UBC and 14 patients with ABC that were surgically treated by curettage and bone grafting in our clinic between 2006-2013. Mean age was 19.80 (range, 4-50) years in the patients with UBC and 21.76 (range, 4-56) in the patients with ABC. The diagnosis of the cysts was established both clinically and radiologically. Mean follow-up period was 36 (range, 6-60) months both in the patients with UBC and ABC. The patients with recurrence underwent a second curettage and grafting procedure. Healing and recurrence were evaluated according to modified Neer's scale. Results: Recurrence occurred in 8 patients. Of these, 5 patients underwent a second curettage and grafting procedure and 3 patients were lost to follow-up. Complete healing occurred in all the patients that underwent a second curettage and grafting procedure. Conclusion: The achievement of complete healing in the patients that underwent a second curettage and grafting procedure indicates that the recurrence of UBC and ABC is associated with insufficient curettage. s
Keywords: Unicameral bone cysts; aneurysmal bone cysts; curettage; healing